Variable-rate adaptive trellis coded QAM for flat-fading channels. - Lau, V.K.N.
A bandwidth-efficient variable-rate adaptive channel coding scheme, ATCQAM, for time-varying flat-fading channels is proposed. In addition to the forward channel, a low-capacity feedback channel is needed to convey channel state information to the transmitter, possibly with delays and noise. A number of transmission modes, with varying throughputs, are incorporated at the transmitter. Appropriate transmission modes are selected based on the feedback channel states. Design issues for the ATCQAM are considered. A closed-loop control scheme to maintain mode synchronization between the transmitter and the receiver is discussed. The effects of feedback delay, a noisy feedback channel, and mobile speed are investigated. Analytical bounds are derived and simulations are performed to verify the results
Keywords: ATCQAM; Analytical bounds; Bandwidth-efficient variable-rate adaptive channel coding; Channel state information; Closed-loop control scheme; Delays; Feedback channel state; Feedback delay; Flat-fading channels; Forward channel; Low-capacity feedback channel; Mobile speed; Mode synchronization; Noise; Noisy feedback channel; Receiver; Throughputs; Time-varying flat-fading channels; Transmission modes; Transmitter; Variable-rate adaptive trellis coded QAM